2020
DOI: 10.1111/ahg.12398
|View full text |Cite
|
Sign up to set email alerts
|

NCAPH is upregulated in endometrial cancer and associated with poor clinicopathologic characteristics

Abstract: Background: Recently, NCAPH (non-SMC condensin I complex subunit H), a regulatory subunit of the condensin complex, has captured our attention in various cancer studies. However, the function of NCAPH in endometrial cancer (EC) remains unclear. Our study aims to investigate the role of NCAPH in EC. Methods: The expression of NCAPH in EC tissues and normal tissues was predicted by The Cancer Genome Atlas (TCGA). The Kaplan-Meier analysis was performed to evaluate the impact of NCAPH expression on EC patients' s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…NCAPH has been demonstrated to be elevated in a large amount of human cancers. In endometrial cancer, significantly upregulated NCAPH expression is observed in clinical tissues when compared to the normal tissues, which is associated with poor clinicopathologic characteristics [ 9 ]. Another study has determined that aberrantly high NCAPH overexpression is required for proliferation, migration, and invasion of non-small cell lung cancer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NCAPH has been demonstrated to be elevated in a large amount of human cancers. In endometrial cancer, significantly upregulated NCAPH expression is observed in clinical tissues when compared to the normal tissues, which is associated with poor clinicopathologic characteristics [ 9 ]. Another study has determined that aberrantly high NCAPH overexpression is required for proliferation, migration, and invasion of non-small cell lung cancer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instances, NCAPH is significantly upregulated in prostate cancer, and NCAPH silencing suppresses cell proliferation and metastasis [ 6 , 7 ]. Compelling evidence indicates that NCAPH functions as an oncogene in endometrial cancer and breast cancer, and its highly expression represents a poor prognosis [ 8 , 9 ]. Zhan et al firstly demonstrated that NCAPH is upregulated in serous ovarian cancer, which might be involved in the carcinogenesis of this disease and carboplatin resistance, providing a potential prognostic indicator for patients with carboplatin resistance in serous ovarian cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that NCAPH is involved in the progression of several types of cancer. A recent study reported that NCAPH was significantly upregulated in endometrial cancer (EC), thus acting as an oncogene to promote the development of EC ( 11 ). Another study indicated that NCAPH knockdown could inhibit cell proliferation, migration and invasion and induce cell cycle arrest in non-small cell lung cancer (NSCLC) ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Qiu et al, first reported that the mRNA of NCAPH was overexpressed in EC and was associated with unfavorable clinicopathologic features and a bad prognosis. Upregulation of NCAPH expression was significantly associated with hypomethylation [ 54 ]. Hua and colleagues used a variety of databases to describe a series of changes in MCM in EC, and they concluded that the mRNA and protein levels of MCMs were greatly increased in individuals with EC, while the average methylation level in the promoter region of MCM was dramatically reduced [ 55 ].…”
Section: Oncogenesmentioning
confidence: 99%